Pengaruh Media Sosial Terhadap Peningkatan Kejahatan Siber dan Tantangan Penegakan Hukum Pidana - Iswandy Rani Saputra; Rachman Rizal A. Sapada; A. Dzulqarnain; Suprapto Suprapto (Faculty of Law Andi Sapada Institute of Social Sciences and Business, 2025)
This study discusses the influence of social media on the increase in cybercrime in Indonesia and the challenges of criminal law enforcement in dealing with it. Using normative legal research methods, this study analyses applicable regulations, technical barriers, and social dynamics that affect the effectiveness of law enforcement against cybercrime, especially those that originate from activities on social media. The study results show that the high penetration of social media, low digital literacy, and the development of increasingly complex crime modes have encouraged an increase in cybercrime cases. On the other hand, law enforcement still faces regulatory limitations, a lack of competent human resources, cross-border jurisdictional challenges, and weak coordination between agencies. This research recommends adaptive regulatory reforms, capacity building of law enforcement officials, strengthening national and international cooperation, and public digital literacy education to create a safer and more equitable digital ecosystem.